Development of a Wheel and Axle System Using a Resonating Spring for a Power Generation - Jasper A., Agbakwuru; A.O., Ibhadode Akii (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
A new technique is developed that provides an increment in torque without necessarily reducing speed. The increase in the torque and the ability of the machine to retain approximately the same speed means an increase in the mechanical power. The consequence of this technology is vast application of low speed high torque machine to produce power using high speed running gear box system. It could also be useful to operate fuelless vessels that could be used to ply offshore waters. The research has given a better insight that extra power can be injected into a mechanical system by a simple resonance of spring loadings. It is now known that energy can be sustained without much loss by the effect of spring resonance. This is a huge variation of the present state-of-the-art of using gear transmission systems.